Influence of protein source fed to the earlyweaned pig during phase I (D 0 - 9) on the responses to various protein sources fed during phase II (D 9 - 28) - Kats, L.J.; Hansen, J.A.; Tokach, Michael D.; Nelssen, Jim L.; Goodband, Robert D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 468 weanling pigs (initially 13.2 lb and 21 d of age) was used in a 28 d growth assay to determine the influence of protein source fed during phase I (d 0 to 9) on the response to various protein sources fed during phase II (d 9 to 28). Phase I diets contained 20% dried whey, 10% lactose, and either 10.3% spray-dried porcine plasma or 15.2% moist-extruded soy protein concentrate and formulated to contain 1.5% lysine. On d 9, pigs were switched to diets containing 10% dried whey and either 3.9% spraydried porcine plasma, 2.5% spray-dried blood meal, or 5.7% moist-extruded soy protein concentrate and formulated to contain 1.25% lysine. During phase I, pigs fed spray-dried porcine plasma had improved average daily gain (.30 vs .16 lb), average daily feed intake (.40 vs .29 Ib), and feed efficiency (1.35 vs 2.08) compared to pigs fed moist-extruded soy protein concentrate. During phase II, pigs fed diets containing spray-dried porcine plasma had increased average daily gain and average daily feed intake compared with pigs fed diets containing spray-dried blood meal and higher average daily feed intake than pigs fed extruded soy protein concentrate. There were no interactive effects between phase I and phase II protein sources; therefore, growth responses observed during phase I apparently are additive with those observed during phase II.
Keywords: Swine; Starter; Protein Source; Performance